Analysis of Markers for Combustion Mode and Heat Release in MILD Combustion Using DNS Data. Issue 5 (3rd June 2019) - Doan, N.A.K; Swaminathan, N.
ABSTRACT: Various commonly used markers for heat release are assessed using direct numerical simulation (DNS) data for Moderate or Intense Low-oxygen Dilution (MILD) combustion to find their suitability for non-premixed MILD combustion. The laser-induced fluorescence (LIF) signals of various markers are synthesized from the DNS data to construct their planar (PLIF) images which are compared to the heat release rate images obtained directly from the DNS data. The local OH values in heat releasing regions are observed to be very small compared to the background level coming from unreacted mixture diluted with exhaust gases. Furthermore, these values are very much smaller compared to those in burnt regions. This observation rises questions on the use of OH-PLIF for MILD combustion. However, the chemiluminescent image obtained using O H ∗ is shown to correlate well with the heat release. Two scalar-based PLIF markers, O H × C H 2 O and H × C H 2 O, correlate well with the heat release. Flame index (FI) and chemical explosive mode analyses (CEMA) are used to identify premixed and non-premixed regions in MILD combustion. Although there is some agreement between the CEMA and FI results, large discrepancies are still observed. The schlieren images deduced from the DNS data showed that this technique can be used for a quick and qualitative identification of MILD combustion before applying expensive laser diagnostics.